Serum ionized magnesium acts as an independent protective factor against bone erosion in patients with gouty arthritis: a cross-sectional study - Li, Yixuan; Wang, Yahao; Xu, Lili; Liu, Chuanfeng; Cui, Jiufa; Huang, Yajing; Li, Shufa; Wang, Yangang; Dong, Bingzi (Frontiers in Endocrinology, 2024)
Gouty arthritis is a common inflammatory arthritis. The recurrent gout attacks severely damage the joint's function, lead to bone erosion, and affect bone metabolism. The role of magnesium (Mg) ions in bone homeostasis has been recognized, whereas its specific relationship with gouty bone erosion remains unclear. This study examined the association between serum ionized Mg levels and bone erosion in patients with gout arthritis.A total of 769 patients with gout arthritis were included in the study. Participants were classified into four groups based on the quartiles of the serum ionized Mg level. Logistic regression analysis assessed the association between serum ionized Mg and bone erosion.Compared to patients without bone erosion, serum ionized Mg levels were lower in gout patients with bone erosion (p<0.001). When dividing serum ionized Mg into quartiles, the prevalence rate of bone erosion in group Q1, representing the patients with the lowest serum ionized Mg levels, was notably higher than in Q2, Q3, and Q4 (60.2% vs. 43.6%, 45.6%, 40.3%, p<0.001). Multiple logistic regression analysis revealed that patients in Q2-Q4 had a lower odds ratio (OR) of bone erosion compared to those in Q1 (ORs were 0.520, 0.533, and 0.411 in Q2-Q4, respectively, p<0.001).The incidence of bone erosion is higher in gout arthritis patients with lower serum ionized Mg levels. High serum ionized Mg levels may be an independent protective factor for bone erosion in gout arthritis. Thus, Mg supplementation may be a promising approach to prevent or slow down the development of bone erosion in gouty arthritis.